A rare case of disseminated sarcoidosis presenting with neurosarcoidosis: A case report - Sukur N.A.; Sahari N.S.; Marwan A.Z.; Ismail R. (Universiti Putra Malaysia Press, 2024)
Indexed by SCOPUS/MYCITE